Application of response surface methodology in describing the performance of coated carbide tools when turning AISI 1045 steel - Noordin, M. Y.; Venkatesh, V. C.; Sharif, S.; Elting, S.; Abdullah, A. (Elsevier B V, 2004)
The performance of a multilayer tungsten carbide tool was described using response surface methodology (RSM) when turning AISI 1045 steel. Cutting tests were performed with constant depth of cut and under dry cutting conditions. The factors investigated were cutting speed, feed and the side cutting edge angle (SCEA) of the cutting edge. The main cutting force, i.e. the tangential force and surface roughness were the response variables investigated. The experimental plan was based on the face centred, central composite design (CCD). The experimental results indicate that the proposed mathematical models suggested could adequately describe the performance indicators within the limits of the factors that are being investigated. The feed is the most significant factor that influences the surface roughness and the tangential force. However, there are other factors that provide secondary contributions to the performance indicators. In the case of surface roughness, the SCEA2 and the interaction of feed and SCEA provides these contributions whilst for tangential force, the SCEA2, the interaction of feed and SCEA; and the cutting speed provides them.